Detection of DNA A and DNA Î² associated with cotton leaf curl and some other plant diseases caused by whitefly transmitted geminiviruses - and A. VARMA*, G. RADHAKRISHNAN, V.G. MALATHI (Indian Phytopathology, 2004)
Recent outbreak of cotton leaf curl disease, caused by whitefly transmitted Cotton leaf curl Rajasthan virus (CLCuRV), is a major threat to cotton production in the North-West India. For rapid and sensitive diagnosis of CLCuRV nucleo-diagnostic methods have been developed. Nucleic acid spot hybridization (NASH), using radio-labeled probes to CLCuRV DNA-A and CLCuRV DNA Î², was found efficient in detecting CLCuRV both in plants and viruliferous whiteflies. These probes also detected infection by other whitefly transmitted geminiviruses (WTGs) in crop, ornamental and weed plants. Hybridization of DNA Î² probe with plant samples naturally infected with other WTGs shows that the association of DNA Î² molecules could be a common feature of WTGs in northern India. CLCuRV was also efficiently detected by PCR using primers to amplify coat protein gene and full length DNA Î’molecules from infected plants and viruliferous whiteflies; subgenomic DNA Î’forms were also amplified from CLCuRV infected test hosts and viruliferous whiteflies. The number of sub-genomic forms of DNA Î² varied in different hosts.